Employee Engagement as a Pathway to Employee Retention: The Role of Employee Well-being and Work-Life Balance in the Banking Sector : JEL Classification: M12; M51; J28; J63; G21 - Marsuki Marsuki; Yuswari Nur (Newinera Publisher, 2026)
Employee retention has become an important challenge in the banking industry amid digital transformation and changing workforce expectations. This study examines the effects of Employee Well-being and Work-Life Balance on Employee Retention through Employee Engagement among employees of BNI Makassar. A quantitative approach was employed using survey data collected from 148 employees selected from a population of 235 employees. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings reveal that Employee Well-being and Work-Life Balance positively and significantly affect Employee Engagement and Employee Retention. Employee Engagement also has a significant positive effect on Employee Retention and partially mediates the relationships between Employee Well-being and Employee Retention as well as between Work-Life Balance and Employee Retention. Employee Well-being emerged as the strongest predictor of Employee Retention. These findings indicate that organizational efforts to improve employee welfare, create a supportive work environment, and promote work-life balance can strengthen employee engagement and enhance retention. The study contributes to the human resource management literature by providing empirical evidence on employee retention mechanisms in the banking sector and offers practical implications for developing sustainable human resource strategies.